Did the house mouse (Mus musculus L.) shape the evolutionary trajectory of wheat (Triticum aestivum L.)?. Issue 10 (28th August 2013) - Morris, C. F.; Fuerst, E. P.; Beecher, B. S.; Mclean, D. J.; James, C. P.; Geng, H. W.
Abstract Wheat (Triticum aestivum L.) is one of the most successful domesticated plant species in the world. The majority of wheat carries mutations in the Puroindoline genes that result in a hard kernel phenotype. An evolutionary explanation, or selective advantage, for the spread and persistence of these hard kernel mutations has yet to be established. Here, we demonstrate that the house mouse (Mus musculus L.) exerts a pronounced feeding preference for soft over hard kernels. When allele frequencies ranged from 0.5 to 0.009, mouse predation increased the hard allele frequency as much as 10‐fold. Studies involving a single hard kernel mixed with ~1000 soft kernels failed to recover the mutant kernel. Nevertheless, the study clearly demonstrates that the house mouse could have played a role in the evolution of wheat, and therefore the cultural trajectory of humankind.